2021
DOI: 10.1002/prot.26257
|View full text |Cite
|
Sign up to set email alerts
|

Applying and improving AlphaFold at CASP14

Abstract: We describe the operation and improvement of AlphaFold, the system that was entered by the team AlphaFold2 to the "human" category in the 14th Critical Assessment of Protein Structure Prediction (CASP14). The AlphaFold system entered in CASP14 is entirely different to the one entered in CASP13. It used a novel end-toend deep neural network trained to produce protein structures from amino acid sequence, multiple sequence alignments, and homologous proteins. In the assessors' ranking by summed z scores (>2.0), A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
201
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(203 citation statements)
references
References 24 publications
(35 reference statements)
2
201
0
Order By: Relevance
“…We hypothesized that the predicted IDRs with high pLDDT scores might manifest for one or a combination of reasons: (1) global amino-acid sequence differences in comparison to the predicted IDRs with low pLDDT scores, (2) relatively high positional sequence conservation (i.e., “high quality” multiple sequence alignments (MSA)), and (3) the enrichment of high-pLDDT IDR sequences in the PDB. The first possibility would reflect a differential “folding propensity” that is inherently encoded in the amino-acid sequences of high vs. low pLDDT-scoring IDRs, whereas the latter two possibilities would influence the AlphaFold2 prediction confidence due to the depth of the MSAs (2) or sequence similarity to the structures from the PDB used in training (3) (Jumper et al 2021a,b). Given the relatively poor coverage of IDRs in the PDB (Quaglia et al 2021) and the poor positional alignability for most IDRs (Colak et al 2013; Nguyen Ba et al 2012; Zarin et al 2019, 2021), it is plausible that some combination of all three of the aforementioned possibilities could contribute to high pLDDT scoring IDRs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesized that the predicted IDRs with high pLDDT scores might manifest for one or a combination of reasons: (1) global amino-acid sequence differences in comparison to the predicted IDRs with low pLDDT scores, (2) relatively high positional sequence conservation (i.e., “high quality” multiple sequence alignments (MSA)), and (3) the enrichment of high-pLDDT IDR sequences in the PDB. The first possibility would reflect a differential “folding propensity” that is inherently encoded in the amino-acid sequences of high vs. low pLDDT-scoring IDRs, whereas the latter two possibilities would influence the AlphaFold2 prediction confidence due to the depth of the MSAs (2) or sequence similarity to the structures from the PDB used in training (3) (Jumper et al 2021a,b). Given the relatively poor coverage of IDRs in the PDB (Quaglia et al 2021) and the poor positional alignability for most IDRs (Colak et al 2013; Nguyen Ba et al 2012; Zarin et al 2019, 2021), it is plausible that some combination of all three of the aforementioned possibilities could contribute to high pLDDT scoring IDRs.…”
Section: Resultsmentioning
confidence: 99%
“…The biennial Critical Assessment of Structure Prediction (CASP) competition (Moult et al 1995) has stimulated many developments in the field of protein structure prediction, including the successful implementation of co-evolutionary restraints derived from multiple sequence alignments (MSAs) and machine learning protocols in CASP12 (Moult et al 2018; Schaarschmidt et al 2018). CASP14 brought a revolutionary advancement: the AlphaFold2 team at DeepMind produced more models with atomic-level accuracy than ever before in the history of CASP (AlQuraishi 2021; Jumper et al 2021a,b). The second-best scoring prediction software in CASP14 led to the RoseTTAFold structure prediction platform, which was released in open-source format and contained a webserver for ease of access (Baek et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, only one of the five multimer DL models generated such a model by using unpaired MSAs. It appears that using unpaired MSAs may be the key for generating this good model, because runs with paired MSAs by following the AF-Multimer workflow return unphysical models with severe clashes, a phenomenon akin to “chain collapse” observed previously[3]. Paired MSAs may have contributed to the issue.…”
Section: Supplementary Informationmentioning
confidence: 86%
“…In the 2020 Critical Assessment of Protein Structure Prediction (CASP14), the DeepMind AlphaFold2 (AF2) deep learning method (Jumper et al, 2021a; Jumper et al, 2021b) demonstrated outstanding performance in blind predictions of protein structure, delivering excellent structural matches to experimental models derived from X-ray crystallography, NMR and cryoEM data, over a wide range of target difficulty (Kryshtafovych et al, 2021). These AlphaFold2 model predictions had an unprecedented high accuracy, assessed by backbone atomic coordinate global distance test (GDT_TS) scores.…”
Section: Introductionmentioning
confidence: 99%